Improving mechanical properties of constrained friction processing Mg-Zn-Ca alloys by modifying texture using multiple pass processing - Chen, Ting; Fu, Banglong; Suhuddin, Uceu F. H. R.; Shen, Tong; Li, Gaohui; Maawad, Emad; Shen, Junjun; Santos, F. dos Jorge; Bergmann, Jean Pierre; Klusemann, Benjamin (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Constrained Friction Processing (CFP), a novel friction-based technique, has been developed to efficiently process fine-grained magnesium (Mg) rods, expanding the potential applications of biodegradable Mg alloys in medical implants. This study investigates the enhancement of mechanical properties through the implementation of multiple pass CFP (MP-CFP) in comparison to the conventional single pass CFP. The results reveal a substantial improvement in compressive yield strength (CYS), ultimate compressive strength, and failure plastic strain by 11 %, 28 %, and 66 %, respectively. A comprehensive analysis of material evolution during processing and the effects of the final microstructure on mechanical properties was conducted. The intricate material flow behavior during the final plunge stage of MP-CFP results in a reduced intensity of local basal texture and macrotexture. The diminished intensity of basal texture, combined with a low geometrical compatibility factor at the top of the rod after MP-CFP, effectively impedes slip transfer across grain boundaries. This leads to a local strain gradient along the compression direction, ultimately contributing to the observed enhancement in mechanical properties. The Mg-0.5Zn-0.3Ca (wt.%) alloy, after texture modification by MP-CFP, exhibits a competitive CYS compared with other traditional methods, highlighting the promising application potential of MP-CFP.
Keywords: Constrained Friction Processing; Magnesium Alloy; Microstructure; Mechanical Property; Texture; Plastic Deformation